Ethnomedicinal knowledge of the rural communities of Gulmarg, Jammu and Kashmir, India (Asian Journal of Ethnobiology, 2023)
Abstract. Ji A, Hamid A, Andrabi SAH. 2023. Ethnomedicinal knowledge of the rural communities of Gulmarg, Jammu and Kashmir, India. Asian J Ethnobiol 6: 58-64. In the current study, 60 medicinal plants have been collected from Gulmarg, Jammu and Kashmir (India), belonging to 34 families. The plant parts used were dominated by roots (36%), and the collection of roots has depleted the population of certain plant and may endanger the survival of the rare and slowly reproducing medicinal plants. It was found that the old people possessed a good wealth of traditional information as compared to younger generation Therefore, it is imperative to document the medicinal plants and associated information and to require necessary measures for the conservation of those resources. Herbs dominated all other life forms (49 species). The most typical way to consume the medications was by decoction, 32% (22 species). According to the current study the most prevalent disease addressed by the medicinal plants included was gastrointestinal disorders (25 species). Artemisia absinthium L. had the highest Use Value (UV), i.e., 0.58, while Viscum album L. had the lowest UV (0.17). Locals continue to value herbal treatments as a trustworthy means of curing a variety of ailments.
Keywords: Ethnomedicine, Gulmarg, medicinal plants, traditional knowledge